Analysis of Factors Influencing the Compliance of Motor Vehicle Taxpayer at Samsat Depok 1 - Nazzala Yunika Nurrizqi; Tresno Eka Jaya; Hera Khairunnisa (RTTM, 2025)
This research is motivated by the significant role of motor vehicle tax as one of the main sources of regional revenue. However, the compliance level of motor vehicle taxpayers remains a significant challenge that requires further research. This research aims to analyze the factors that influence the compliance of motor vehicle taxpayers registered at the Samsat Office of Depok City 1. This research adopts a quantitative approach, with data collected by distributing questionnaires to 150 respondents selected using a convenience sampling technique. The data were analyzed using multiple linear regression with SPSS 26. The results showed that taxpayer awareness, tax service quality, and tax sanctions had a positive effect on the compliance of motor vehicle taxpayer. Meanwhile, subjective norms have a negative effect on the compliance of motor vehicle taxpayer. This research contributes by providing empirical evidence regarding the factors that can influence the compliance of motor vehicle taxpayers. The results of this study can be used as a consideration in formulating policies that can enhance the compliance of motor vehicle taxpayers at the Samsat Office of Depok City 1.